FOTOVOLTAİK DESTEKLİ ABSORBSİYONLU SOĞUTMA SİSTEMİ TASARIMI - DOĞAN, DAMLA (Fırat Üniveristesi, 2018)
Dünya ülkelerinin temel ihtiyaçlarından biri enerji kaynaklarıdır. Yenilebilir enerji kaynaklarından olan güneş enerjisi her yerde bulunabilen bir enerji olup, çevreye zarar vermemesi nedeniyle önemli bir yere sahiptir. Bu nedenlerden dolayı fosil yakıtlara göre daha çok avantaja sahip olan güneş enerjisi önemli enerji kaynaklarından biri haline gelmiştir. Bu yönde yenilebilir enerji kaynaklarının kullanılması önemli olup, fotovoltaik panel sistemleri ile ilgili çalışmalar hız kazanmıştır. Bu çalışmada, fotovoltaik panel destekli absorbsiyonlu soğutma sisteminin ısıl analizinin yapılması hedeflemiştir.

One of the basic needs of the world's countries is energy resources. Solar energy from renewable sources of energy is an energy that can be found everywhere and it has an important place because it does not harm the environment. Because of these reasons, solar energy, which has more advantages than fossil fuels, has become one of the important energy sources. The use of renewable energy sources is important in this respect and the studies about photovoltaic battery systems have gained speed. In this study, thermal analysis of photovoltaic battery assisted absorption cooling system was aimed. For this purpose, in this work, an absorbent cooling system combined with photovoltaic battery is designed. The radiation, temperature and current values were determined by conducting experiments with the combined system. The results obtained are transferred to the graphs and the results are interpreted
Design of a photovoltaic assisted absorption cooling system
Keywords: Makine Mühendisliği